Analysis of the positive results and influencing factors of hepatitis B antibody in hospitalized neonates with AgHBs positive mothers - Min, Yu xiao; Gao, Ying; Liu, Chun tian; Lu, Xiao yu; Chen, Xiao chun (Frontiers in Pediatrics, 2022)
Purpose To investigate the effect and influencing factors of the three-injection hepatitis B vaccination during hospitalization and after discharge of neonates whose mothers are hepatitis B infected. Method Adopt convenient sampling method, Neonates born in the obstetrics department of a tertiary first-class hospital in Wenzhou City, Zhejiang Province, China from January 2018 to April 2021 and admitted to the NICU were selected as the research subjects. According to the serological test results, the newborns were divided into two groups: antibody positive and negative, and the influencing factors of hepatitis B vaccination were retrospectively analyzed. Result A total of 333 cases were serologically tested, of which 269 cases (80.78%) were antibody positive and 64 cases (19.22%) were antibody negative.The results of binary Logistic regression analysis showed that: Whether the vaccination was completed on time after discharge ( OR = 12.659 ), whether the full-term vaccination was completed ( OR = 7.175 ), and white-ball ratio ( OR = 9.792 ) were the protective factors for the production of hepatitis B antibodies in hospitalized neonates. Hepatitis B immunoglobulin injection time > 6 h ( OR = 0.213 ) and combined immunization time > 12 h ( OR = 0.024 ) were risk factors ( P < 0.05 ). Conclusion 19.22% of neonates who were hospitalized could not produce HBV surface antibodies after three doses of hepatitis B vaccination were completed. It is recommended that the three-injection vaccination is completed on time after hospitalized neonates are discharged. Improve the neonatal vaccination process, and combine immunization as soon as possible after birth.